Frequency of Cutaneous Leishmaniasis and Species Identification in Suspected Individuals from Golestan Province, Northern Iran in 2014 - Farideh HEZARI; Maryam NIYYATI; Seyyed Javad SEYYED TABAEI; Mehdi MOHEBALI; Vahideh MOIN VAZIRI; Hamed BEHNIAFAR; Eznolah AZARGASHB; Niloofar TAGHIPOUR (Tehran University of Medical Sciences, 2016)
Background: Leishmaniasis is a zoonotic disease caused by species of protozoa of the genus Leishmania. In recent years, incidence of cutaneous leishmaniasis has increasing trend in Golestan Province, North of Iran. The aim of the present study was to identify the frequency of cutaneous leishmaniasis using PCR-RFLP in patients referred to Kalaleh Health Center, during 2013-14. Methods: This descriptive cross-sectional study was conducted on 70 individuals with suspected cutaneous leishmaniasis that referred to health center of Kalaleh County, Golestan Province,  Northern Iran, from Sep 2013 to Nov 2014. Samples of cutaneous lesions were examined microscopically. DNA was extracted from all of the positive smears and PCR was done on ITS-1 gene. RFLP was performed using HaeIII enzyme for species identification. Results: Totally, 38 out of the 70 (54.3%) suspected individuals including 22 males (57.9%) were found positive by microscopic examination. All of microscopically positive samples were confirmed to be positive for Leishmania DNA (approximately 340 bp bands were detected). RFLP revealed 140 bp and 200 bp bands (approximate size), indicative of L. major. Conclusion: The detected species of studied region was L. major. Cutaneous leishmaniasis has high prevalence in Kalaleh County, thus more studies on leishmaniasis in the animal reservoirs, comparison of homology of animal and human isolates and a survey regarding natural infection of vectors in this region is highly recommended.